2014
DOI: 10.3855/jidc.5855
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of pneumococcal conjugate vaccines in preventing pneumonia in Peruvian children

Abstract: Introduction: Pneumococcal pneumonia (PP) has a high burden of morbimortality in children. Use of pneumococcal conjugate vaccines (PCVs) is an effective preventive measure. After PCV 7-valent (PCV7) withdrawal, PCV 10-valent (PCV10) and PCV 13-valent (PCV13) are the alternatives in Peru. This study aimed to evaluate cost effectiveness of these vaccines in preventing PP in Peruvian children <5 yearsold. Methodology: A cost-effectiveness analysis was developed in three phases: a systematic evidence search for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…This dominance is in line with various other cost-effectiveness analyses, from Malaysia [ 10 ], Japan [ 57 ], the Philippines [ 27 ], Turkey [ 58 ], Europe [ 20 , 59 61 ], Canada [ 20 ] and Peru [ 53 ]. However, some studies have predicted the reverse: that PCV13 would be dominant over PHiD-CV (Malaysia and Hong Kong [ 11 ], Colombia [ 62 ], Europe [ 63 ] and Canada [ 64 ]) or more cost-effective than PHiD-CV (Peru [ 65 ]). These differences in predicted outcomes are largely due to the assumptions used.…”
Section: Discussionmentioning
confidence: 99%
“…This dominance is in line with various other cost-effectiveness analyses, from Malaysia [ 10 ], Japan [ 57 ], the Philippines [ 27 ], Turkey [ 58 ], Europe [ 20 , 59 61 ], Canada [ 20 ] and Peru [ 53 ]. However, some studies have predicted the reverse: that PCV13 would be dominant over PHiD-CV (Malaysia and Hong Kong [ 11 ], Colombia [ 62 ], Europe [ 63 ] and Canada [ 64 ]) or more cost-effective than PHiD-CV (Peru [ 65 ]). These differences in predicted outcomes are largely due to the assumptions used.…”
Section: Discussionmentioning
confidence: 99%
“…b All pneumococcal sepsis refer to non-pneumonia non-meningitis invasive disease (NPNM). [31]. Also contrasting our findings, GlaxoSmithKline ® (GSK) performed a cost-utility analysis on PCV introduction in Peru whose results suggested that PCV10 was more cost-effective than PCV13 [68].…”
Section: Discussionmentioning
confidence: 84%
“…The approved National Immunization Schedule for PCV7 in Peru included two primary doses at 2 and 4 months of age, plus a booster at 12-18 months (PCV2 + 1) [4,31,32]. Vaccination coverage was assumed based on coverage levels achieved with PCV7 for 2011, which were 99.2% for the first dose, 95.8% for the second and 92.5% for the booster.…”
Section: Vaccination Schedule and Coveragementioning
confidence: 99%
“…En respuesta a esta necesidad de evidencia del MINSA el INS realizó dos evaluaciones económicas. El primer estudio demostró que la vacuna VCP13 es más costo efectiva que la VCP10 para prevenir neumonía en niños menores de cinco años en Perú (18,19) . El segundo estudio extendió el análisis a otras afecciones: otitis media y meningitis encontrando similares resultados (20,21) .…”
Section: Evidencia Para Tomar Decisiones De Políticas Y Programas Nacunclassified